Multitasking and aging: Do older adults benefit from performing a highly practiced task? - Allen, Philip A.; Lien, Mei-Ching; Ruthruff, Eric; Voß, Andreas (Experimental aging research, 2014)
Background/Study Context: The present study examined the effect of training on age differences in performing a highly practiced task using the psychological refractory period (PRP) paradigm (Pashler, 1984, Journal of Experimental Psychology: Human Perception and Performance, 10, 358-377). Earlier training studies have concentrated on tasks that are not already overlearned. The present question of interest is whether task dual-task integration will be more efficient when single-task performance is approaching asymptotic levels.Methods: Task 1 was red/green signal discrimination (green = “go” and red = “wait”; analogous to pedestrian signals) and Task 2 was tone discrimination (white noise vs. a horn “honk”; analogous to traffic sound). The stimulus onset asynchrony (SOA) between Task 1 and Task 2 was varied (50, 150, 600, and 1000 ms). All individuals participated in eight sessions spread over 8 weeks (one session per week). Participants completed a dual-task pretest (Week 1), followed by 6 weeks of single-task testing (Weeks 2-7), followed by a dual-task posttest (Week 8).Results and Conclusion: Although older adults showed larger overall dual-task costs (i.e., PRP effects), they were able to reduce the costs with practice as much as younger adults. However, even when training on Task 1 results in asymptotic performance, this still did not lead to an appreciable reduction in dual-task costs. Also, older adults, but not younger adults, responded more rapidly to green stimuli than to red stimuli in the Task 1 training latency data. The authors confirmed this green/go bias using diffusion modeling, which takes into account response time and error rates at the same time. This green/go bias is potentially dangerous at crosswalks, especially when combined with large dual-task interference, and might contribute to the high rate of crosswalk accidents in the elderly.
Gesehen am 30.07.2020